PENINGKATAN HASIL BELAJAR DAN KEAKTIFAN PESERTA DIDIK KELAS X MIPA 1 SMAN 9 KOTA BENGKULU PADA MATERI STOIKIOMETRI KIMIA DENGAN MODEL PEMBELAJARAN PBL - yetmi, Yetmi; Melani, Iim; Apriyoanda, Hadi; Handayani, Dewi (ALOTROP, 2023)
Classroom Action Research (CAR) aims to improve learning outcomes and student engagement by utilizing the Problem-Based Learning (PBL) instructional model in Class X MIPA 1 at SMAN 9 in Bengkulu City. The CAR was conducted in May 2023 over 2 cycles. Each cycle comprises 1 session, spanning 3 instructional hours (3 x 45 minutes). The phases of each cycle commence with observations to diagnose issues, followed by design, implementation, event observation, evaluation, and reflection. Based on the results of the conducted data analysis, it was determined that the application of the PBL learning model was able to demonstrate an increase in learning outcomes and student engagement in Cycle 2. The average student learning outcomes improved from 77.66% to 59.38%, accompanied by an increase in the percentage of students achieving competency, from 85.47% to 81.25%. Student participation during the learning process also saw an increase in Cycle 2. Student engagement rose from 66.74% in the moderate category to 78.28% in the high category. Keywords: Learning outcomes, engagement, and PBL